Strategic Communication and Public Engagement: The UAE E-Brainstorming Session - Badran A. Badran (Department of Communications, Universitas Islam Indonesia, 2017)
In the context of the conference’s topic of ‘Strategic Communication and Public Engagement’ comes this case study, which illustrates the creative use of social media in crowdsourcing ideas from the public with the goal of formulating government policy in the United Arab Emirates (UAE). Unlike the usual model of top-down policy formulation in many developing countries, the UAE government adopted an experiment entitled ‘The UAE Brainstorming Session’, which is the country’s first technology-based citizen engagement event that leveraged the highly popular social media platforms to elicit ideas and suggestions about public services. Specifically, two under-performing national sectors were targeted; public health and education. Citizens and residents were invited to identify the main issues in these two sectors and offer their suggestions to address them. The UAE Prime Minister personally tweeted inviting everyone to participate. The public response to this initiative was substantial, with 82,000 new ideas delivered by several social media channels. A ministerial committee then shortlisted the best ideas, suggestions, and these were subsequently discussed in a strategic cabinet retreat. The next step was government approval of several initiatives, which were subsequently implemented. Lessons learned from this case study can be beneficial to many countries that are considering similar technology-based initiatives that utilize popular and accessible social media as public policy tools and instruments of citizen engagement.Keywords: Strategic Communication; Citizen Engagement; Social Media; United Arab Emirates Government.